2013
DOI: 10.1001/jamadermatol.2013.741
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Laminin-332 Mucous Membrane Pemphigoid Developing After a Diphtheria Tetanus Vaccination

Abstract: accine administration is an effective tool to prevent infectious diseases, but its powerful stimulus on the immune system has generated the fear of exacerbating preexisting autoimmune diseases or inducing autoimmune disorders in otherwise healthy individuals.1 Bullous pemphigoid (BP) is the most frequent autoimmune blistering skin disease. It affects predominantly elderly individuals but has also been reported in children. The etiologic characteristics of BP are unknown, but there have been 26 BP cases suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…41,42 EMM, unlike SJS/TEN, is recurrent in the absence of reexposure to the initial inciting event. 43 Other rare delayed cutaneous reactions potentially associated with vaccines have been reported (Table 2) and include acute generalized exanthematous pustulosis, 44,45 erythema nodosum, [46][47][48][49] granuloma annulare, 50 bullous pemphigoid, [51][52][53] Sweet's syndrome, [54][55][56][57][58][59] Gianotti-Crosti syndrome, 60 lichenoid eruptions, 46,50,61-66 cutaneous lupus, 46,67 lupus vulgaris [68][69][70] and serum sickness-like reactions. [71][72][73][74][75][76] Similar to vaccine associated EMM, the presence of an ongoing infection prior to both vaccination and the development of these cutaneous syndromes is frequently reported in these cases.…”
Section: Polysorbates/polyethylene Glycolsmentioning
confidence: 99%
“…41,42 EMM, unlike SJS/TEN, is recurrent in the absence of reexposure to the initial inciting event. 43 Other rare delayed cutaneous reactions potentially associated with vaccines have been reported (Table 2) and include acute generalized exanthematous pustulosis, 44,45 erythema nodosum, [46][47][48][49] granuloma annulare, 50 bullous pemphigoid, [51][52][53] Sweet's syndrome, [54][55][56][57][58][59] Gianotti-Crosti syndrome, 60 lichenoid eruptions, 46,50,61-66 cutaneous lupus, 46,67 lupus vulgaris [68][69][70] and serum sickness-like reactions. [71][72][73][74][75][76] Similar to vaccine associated EMM, the presence of an ongoing infection prior to both vaccination and the development of these cutaneous syndromes is frequently reported in these cases.…”
Section: Polysorbates/polyethylene Glycolsmentioning
confidence: 99%
“…However, cases following non-influenza vaccinations have been rarely reported (Table 1). [1][2][3][4][5][6] Some reports indicated that vaccination may trigger pemphigoid diseases. All patients developed skin lesions after the vaccination, while time of disease onset after vaccination was variable from 1 day to a few weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The etiopathogenesis is still unknown; however, it is thought that environmental factors combined with genetic susceptibility lead to CP. There have been some reported cases of CP triggered by human immunodeficiency virus, diphtheria vaccination, and some medications such as methyldopa, clonidine, and D-penicillamine [110,111]. In addition, other autoimmune diseases may occur more frequently in patients with CP [112].…”
Section: Etiopathogenesismentioning
confidence: 99%